Antenatal Clinical Hypnosis and Birth Ball Exercise as Adjunct Therapy For Management of Labor and Delivery Pain: a Summary of Its Empirical Findings - Aswitami, Ni Gusti Ayu Pramita; Septiani, Ni Gusti Ayu Pitria (Universitas Islam Lamongan, 2020)
Labor pain is conventionally defined similarly to acute pain and exhibits a complex constellation of multiple physiological and psychological factors. Pressure, anxiety, fear, feelings of self-efficacy, coping skills, and social support are influential factors regarding a woman’s perception of pain and labor experiences. This pain varies greatly and often described as the most extreme pain that can be experienced or as agony or like torture that women may go through. Although epidural analgesia is generally accepted to be the gold standard method in intrapartum analgesia, there are risks associated with their use. Any less invasive but effective non-pharmacological approaches that can be used as an analgesic adjunct would be of great importance to the obstetric community. In recent years, clinical hypnosis and birth ball exercise have become an area of increasing clinical interest as methods to help the mother cope with the laboring process. They are frequently applicable, low-cost, and can be used as a supplementary treatment with other medications. Given widespread claims of efficacy, we aimed to review the available evidence regarding its effectiveness as an adjunct therapy for the management of labor and delivery pain. This is important as there is increasing interest among expectant parents and some health care providers about these methods for pain relief during the childbirth process.While many of some investigations show positive effects on the outcome studied, in fact, there are conflicting findings in others showing no statistically significant of its benefits.